(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2022)
Moradabad is situated in western Uttar Pradesh on the Bank of Ram Ganga River and popularly known as PEETAL NAGRI. This city has attained its popularity in the World for exporting valuable gift items, decoration pieces, made up of Iron, copper, silver & gold plated, and mostly of Brass. A survey has been conducted for the quality of drinking water to ensure the contamination of Iron in drinking water sources. Most of the people in Moradabad complain about yellow color in drinking water. This shows poor quality and contamination of water and presence of Iron. 20 water samples have been collected from different locations. 10 water samples have been collected from City (L1 to L10) , 2 samples from Sambhal Road (L11 to L12) , 2 samples from Amroha Road (L13 to L14) , 2 samples from Kanth Road (L15 to L16) and 4 samples from nearby villages on the Kashipur Road (L17 to L20). The concentration level of Iron has been found very high than the maximum permissible limit of 0.3 parts per million (ppm) while other metallic concentration like, Arsenic, Copper, Lead and chromium have been found within permissible limit. In these studies surface water and underground water has been chosen to conduct these studies. In some water samples (L1 to L10) the high concentration of Iron (29.79ppm to 48.14 ppm ) and L11 to L20 8.87pm to 30.09ppm have been found under these studies . The excess of Iron is posing severe health hazards such as liver cancer, diabetes, cirrhosis of liver, and diseases related to heart and nervous system and infertility. It also causes adverse effect on color, odor taste, yellow spots on clothes during washing and accumulation of Iron in pipe lines. This work has been done as a challenge for the welfare of the people of Moradabad. Alternative suggestions have been conveyed to the people of Moradabad to attain healthy life style.